Joint linear precoder optimization and base station selection for an uplink MIMO network: A game theoretic approach - Mingyi Hong; Zhi-Quan Luo (2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2012)
We consider the problem of weighted sum rate optimization in a MIMO interfering multiple access channel (IMAC). We propose to jointly optimize the users' linear procoders as well as their base station (BS) associations. This approach enables the users to avoid congested BSs and can improve system performance as well as user fairness. We formulate the problem into a noncooperative game, and develop an algorithm that allows the players to distributedly reach the Nash Equilibrium (NE) of the game. We show that every NE of the game is a stationary solution of the weighted sum rate optimization problem, and propose an algorithm to compute the NE of the game. Simulation results show that the proposed algorithm performs well in the presence of BS congestion.